Relationship between lentin, insulin resistance, insulin-like growth factor-1 and insulin-like growth factor binding protein-3 in patients with chronic kidney disease - Atamer, A.; Ecder, S. Alisir; Akkus, Z.; Kocyigit, Y.; Atamer, Y.; Ilhan, N.; Ecder, T. (Sage Publications Ltd, 2008)
This study examined the relationship between leptin, insulin-like growth factor-1 (IGF-1), IGF binding protein-3 (IGFBP-3) and insulin resistance in patients with chronic kidney disease (CKD). Levels of leptin, insulin, IGF-1, IGFBP-3 and common routine parameters were measured in 45 patients (23 males and 22 females) with CKD and 45 healthy controls matched for age, gender and body mass index. IGF-1 and IGFBP-3 levels were measured using a two-site immunoradiometric assay. Leptin levels were measured using an enzyme-linked immunosorbent assay. A homeostasis model assessment computer-solved model was used to assess insulin resistance (HOMA-IR). Levels of serum leptin, insulin, IGF-1, IGFBP-3 and HOMA-IR were significantly increased in patients with CKD compared with healthy subjects, whereas fasting blood glucose was not significantly different between the two groups. In patients with CKD, the serum leptin level was significantly correlated with IGF-1, IGFBP-3 and HOMA-IR. In conclusion, this study suggests that there is an interaction between leptin, IGF-1, IGFBP-3 and insulin resistance in patients with CKD.
Keywords: chronic kidney disease; leptin; insulin resistance; insulin-like growth factor-1; insulin-like growth factor binding protein-3